1992
DOI: 10.1080/01904169209364335
|View full text |Cite
|
Sign up to set email alerts
|

Field chlorophyll measurements for evaluation of corn nitrogen status1

Abstract: An experiment was conducted on Norfolk sandy loam soil (Fineloamy, siliceous, thermic Typic Kandiudults) during two years to determine the feasibility of using field chlorophyll measurements for evaluation of corn (Zea mays L.) N status. Nitrogen was applied at rates of 56, 112, 168, 224, 280 and 336 kg ha -1 to establish a range of corn chlorophyll levels, tissue N concentrations, and grain yields. At the V10 and midsilk stages of growth, field chlorophyll measurements were taken with a hand-held chlorophyll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(111 citation statements)
references
References 3 publications
5
103
0
3
Order By: Relevance
“…For example, the leaf chlorophyll content (Cab) and green LAI are often closely related [41], which was also the case for the field data used in the study (Figure 4). As the application of nitrogen increases the chlorophyll content [42], the level of fertilization has an impact on the performance of LAI-sensitive VIs if these also depend on Cab. Furthermore, a similar indirect influence of Cab on the studied VIs is possible if the Cab values are dominated by between-species differences.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the leaf chlorophyll content (Cab) and green LAI are often closely related [41], which was also the case for the field data used in the study (Figure 4). As the application of nitrogen increases the chlorophyll content [42], the level of fertilization has an impact on the performance of LAI-sensitive VIs if these also depend on Cab. Furthermore, a similar indirect influence of Cab on the studied VIs is possible if the Cab values are dominated by between-species differences.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, multiple traits were measured: days to flowering, plant height, and greenness measured using a SPAD 502 Plus Chlorophyll Meter (Spectrum Technologies, Lincoln, NE) on the second, third, and fourth leaves (Wood et al 1992) and averaging the results per plant. In order to assess allometric variability for leaf and canopy components, the second and third fully developed leaves were measured for petiole and leaf-blade length and for width at three equidistant sections along the leaf blade (tip, middle, and basal section).…”
Section: Methodsmentioning
confidence: 99%
“…N content of plant leaves is related to chlorophyll content in plant leaves. Research showed correlations (R) between measured SPAD readings and N content in plant leaves between 0.89 and 0.91 (Wood et al, 1992;Anderson et al, 1993). Within each plot, 20 readings were taken on 20 leaves midway between the collar of the latest fully expanded leaf that had formed at the leaf/stalk junction and the tip of the leaf, and midway between the midrib and edge of the leaf.…”
Section: Chlorophyll Meter Readingsmentioning
confidence: 99%